ANALISIS STRATEGI KONTEN DAKWAH DI INSTAGRAM (STUDI KASUS FAKTOR-FAKTOR YANG MEMPENGARUHI RESPON PENGGUNA PADA AKUN @ISUNSANTRI) - OBIYANTO, AGUNG; BAIHAQI, AGUS; AL FAWWAZ, A. FAIQ (JDARISCOMB: Jurnal Komunikasi dan Penyiaran Islam, 2024)
One of the most important elements in preaching is choosing the media for preaching. One of them is the Instagram account @isunsantri which uses Instagram social media as a media platform for preaching. This research aims to analyze the da'wah content strategy on the @isunsantri Instagram account and the effectiveness of the da'wah content carried out on the @isunsantri account. Using a qualitative approach, this research tests the validity of the data through observation, persistence and triangulation. The results of this research show that the da'wah content strategy carried out on the @isunsantri Instagram account is effective. With evidence from interviews with several followers of the @isunsantri account.